If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 + -8x = 8(-2x + 6) Reorder the terms: 2 + 6x + -8x = 8(-2x + 6) Combine like terms: 6x + -8x = -2x 2 + -2x = 8(-2x + 6) Reorder the terms: 2 + -2x = 8(6 + -2x) 2 + -2x = (6 * 8 + -2x * 8) 2 + -2x = (48 + -16x) Solving 2 + -2x = 48 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 2 + -2x + 16x = 48 + -16x + 16x Combine like terms: -2x + 16x = 14x 2 + 14x = 48 + -16x + 16x Combine like terms: -16x + 16x = 0 2 + 14x = 48 + 0 2 + 14x = 48 Add '-2' to each side of the equation. 2 + -2 + 14x = 48 + -2 Combine like terms: 2 + -2 = 0 0 + 14x = 48 + -2 14x = 48 + -2 Combine like terms: 48 + -2 = 46 14x = 46 Divide each side by '14'. x = 3.285714286 Simplifying x = 3.285714286
| r^2-14r-72= | | 4s+3+90=121 | | m=8-3x | | q^2-7q-10= | | 4(2x+7)=15x+13-7x+15 | | (3)5x-7=(3)15 | | 6x=4(x+6) | | 4+2(5-8)=-12 | | 3(3m+2)=2(3m+3) | | -9m+6=-m+4 | | -35x+14=-6x-60 | | 4+y=4.5 | | 2x+(3x-1)=18+(3x-1) | | 2.25+2y=-17.75 | | -458+(-124)+1025+(-917)+218= | | 3-x/8=-20 | | 7b-45=3b-45 | | -4(x-3)=-12-6x | | y-y=y-y | | 7x-3=x-2 | | 6b+40=-8(-6b-5)+7b | | 0.8(x+100)=0.84x-208 | | 5x^2+4x+9=0 | | mx+4y=3tford | | 7a-6=2a-16 | | 4(4x+1)=16x-5 | | 3(x-5)+8=17 | | 0.4(3z+5)+6.4=0.6(3z-6) | | 22q+53=-145 | | 4x+9x+2-7x=44-x | | 5y+13=17y-95 | | x+40=y-y |